THE INFLUENCE OF THE EXTRAGENT NATURE ON DETERMINATION OF THE NUTRIENT CONTENT IN SOIL - Havrylenko, О.; Sonko, Н.; Zaslavskyi, О.; Stanislaviv, С. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
To provide qualitative assessment of soil resources for their effective utilization it is necessary to harmonize domestic and world methods for analysis of the content of living elements. Carrying out a comprehensive analysis of the soil allows to simulate the processes occurring in it during cultivation of agricultural products and to optimize the amount of fertilizers needed to obtain stable yields. The method used in the research suggested studying the influence of the type of extractant, within the framework of the accepted methods of assessing the quality of validity, on the basis of which the quantities of nutrients in the validity were found. The analysis of the exchange forms of living organisms in the nutrient compounds was carried out using common physical and chemical laboratory methods, namely: pH-metry, spectrophotometry, atomic absorption, semi-wave photometry, and statistical processing of experimental data. We determined the content of macro- and microelements in 7 samples of 123 agrogroups of alkaline black low saline soil, selected in Boryspil district of Kyiv region. The investigation was carried out with the use of different extractants to estimate the efficiency of macro- and microelements extraction from the soil. Analysis of the obtained data confirms the need to conduct the further scientific research in order to create a universal gradation scale. On the basis of the analysis of the obtained data the authors can assert that the methods which are used for agrochemical certification of Ukraine make it possible to receive numerical values of the quantity of elements in the soil which are enough for the assessment of its quality. At the same time, the analysis of some microelements is extremely complicated, due to the catastrophic accumulation of soil on them. Determination of their concentrations requires the use of more efficient extractants and creation of unrefined gradation scales.